1993
DOI: 10.1902/jop.1993.64.9.844
|View full text |Cite
|
Sign up to set email alerts
|

Small Versus Large Particles of Demineralized Freeze‐Dried Bone Allografts in Human Intrabony Periodontal Defects

Abstract: Various particle sizes of demineralized freeze-dried bone allograft (DFDBA) are currently used to treat patients with periodontal osseous defects. However, the effect of particle size on the healing of human intrabony periodontal defects is unknown since there have been no direct clinical comparisons. The purpose of this study was to compare the bony defect resolution obtained using two different particle size ranges of DFDBA. Cortical bone from a single donor was processed and ground to final particle sizes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 6 publications
1
36
0
2
Order By: Relevance
“…With porous graft materials, pore size, pore volume and porosity are important determinants of bone formation 28,29) . The spaces created between the β-TCP particles here seem to have promoted angiogenesis and favored osteoconduction.…”
Section: Discussionmentioning
confidence: 99%
“…With porous graft materials, pore size, pore volume and porosity are important determinants of bone formation 28,29) . The spaces created between the β-TCP particles here seem to have promoted angiogenesis and favored osteoconduction.…”
Section: Discussionmentioning
confidence: 99%
“…20 However, one study stated that there is no significant differences in bony defect fills for two particle sizes tested (250-500 μm & 850-1000 μm). 21 Despite this, the particle size reported to have the best response is 250-750 μm similar to the range used in this study. 22 …”
Section: Discussionmentioning
confidence: 63%
“…[32] found that there was no difference in defect fill between demineralized freeze dried bone allograft particles of 250-500 μm size compared to those of 850-1000 μm. In vitro analysis of the interparticulate space among bone replacement grafts condensed under a uniform standard force showed that autogenous bone harvested low and high speed rotary instruments, freeze dried bone allograft (250-710 μm).…”
Section: Discussionmentioning
confidence: 99%